IMPROVING THE STUDENTS VOCABULARY MASTERY THROUGH MODIFIED DOMINO CARDS AT ELEMENTARY SCHOOL - Nany Soengkono Madayani (Pusat Pengembangan Bahasa IAIN Tulungagung, 2016)
This study examines the use of Modifed Domino Card as an interesting and enjoyable teaching media which has the necessary aspect of competition and forces the learners easy to learn the vocabulary, store it in memory and recall it (Lebedova: 2011) in improving the fifth year students’ vocabulary mastery at Elementary School. The result of the research shows that Modifed Domino Card can improve the students’ vocabulary mastery. There was an improvement on the mean score of the test. In the frst cycle it was 61.38 and improved to 90 in the second cycle. This technique could make the students pay attention to the lesson properly. It also improved students’ participation in learning vocabulary. They were not shy anymore but were highly motivated to join the instructional process. The English teachers who want to apply Modifed Domino Card should prepare the card well and as interesting as possible and do the following steps: (1) dividing students into group, (2) spreading a set of cards to each group, (3) matching the picture and the defnition, and (4) giving test.